2022
DOI: 10.1155/2022/1350673
|View full text |Cite|
|
Sign up to set email alerts
|

Outcome of Extracorporeal Membrane Oxygenation Combined with Intraaortic Balloon Pump Hemodynamic Support during the Percutaneous Coronary Intervention Process for Patients with Cardiac Shock Complicating Acute Myocardial Infarction

Abstract: We evaluate the effect of extracorporeal membrane oxygenation combined with intraaortic balloon pump mechanical circulatory support for patients with cardiogenic shock complicating acute myocardial infarction during the PCI process. Extracorporeal membrane oxygenation combined with intraaortic balloon pump hemodynamic support during the percutaneous coronary intervention process for patients with cardiac shock complicating acute myocardial infarction might play a complementary role. Yet, evidence of applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…pted extensive exploration of its role in optimizing patient outcomes [17][18][19]. ECMO provides a means of maintaining systemic and pulmonary perfusion while allowing for temporary circulatory support, thereby enabling interventionalists to perform complex PCI procedures with enhanced hemodynamic stability [20].…”
Section: E553mentioning
confidence: 99%
See 1 more Smart Citation
“…pted extensive exploration of its role in optimizing patient outcomes [17][18][19]. ECMO provides a means of maintaining systemic and pulmonary perfusion while allowing for temporary circulatory support, thereby enabling interventionalists to perform complex PCI procedures with enhanced hemodynamic stability [20].…”
Section: E553mentioning
confidence: 99%
“…The landscape of PCI has evolved to encompass increasingly complex cases, including high-risk elective interventions [19,33,34]. These cases demand a higher degree of technical expertise and a nuanced understanding of lesion characteristics, hemodynamics, and patient comorbidities [17].…”
Section: Role Of Ecmo In High-risk Pcimentioning
confidence: 99%
“…In general, the evidence indicates that IABP therapy is associated with improved hemodynamics and coronary blood flow. IABP therapy may reduce cardiac afterload and improve diastolic inflow during intra-aortic balloon pumping, thereby providing hemodynamic stabilization and attenuating clinical disturbances of myocardial ischemia [101][102][103].…”
Section: Mechanical Circulatory Supportmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%